POLA AKTIVITAS WISATA BELANJA DI KAMPUNG WISATA KERAMIK DINOYO, MALANG - Joko Triwinarto Santoso; Triandriani Mustikawati; Noviani Suryasari; Ema Y. Titisari (Tesa Arsitektur, 2016)
Dinoyo ceramics tourist kampong has limited space in the effort to organize it. To formulate the concept of spatial planning in accordance with the needs and potential of space, is necessary to identify activity pattern of shopping as a major activity in economic activity that will be developed, as well as the use of space. This study uses observation and behavior mapping of visitors in corridors of the ceramics kampong. Observation time is chosen in rush hours of visitors which are known from questionnaire on the visitors and shop owners. Analysis of observation result and behavioral mapping is conducted by overlay analysis to understand pattern of travel or trip, pattern of activity, and points of visitors activity. While content analysis of the photos/video is performed to determine actors of activity, type of activity, physical order supporting activity, dimension of space, time of occurrence, and duration of activity. The results show that the pattern of shopping activities which occur in the kampong influenced by the type of products, accessibility, availability of parking areas and circulation, as well as the availability of other supporting facilities (signage, maps, location markers, food stalls, public toilets, an information center, etc).